Diagnóstico da produção familiar de leite caprino em Mossoró-RN: aspectos sociais, econômicos, ambientais e higiênico-sanitários - Santos, Caio Sérgio (Universidade Federal Rural do Semi-Árido, 2014)
Dairy goat production is described as an activity with a vocation to the semi-arid northeast, constituting a source of salary and food for family farmers residing in the agrarian reform settlements and traditional rural communities. In the Northeast, the main destination of goat milk produced are school feeding government programs and providing food programs for needy populations, and thus, also tend to encourage family farming. Given the importance of family production of goat milk, this study aimed to characterize this kind of production according to their social, economic, environmental and sanitary-hygienic dimensions in rural farms in Mossoró-RN. The data relating to socioeconomic and environmental aspects were collected with the aid of questionnaires to 29 producers. The sanity aspects were evaluated in 29 properties by the diagnosis of goat mastitis by clinical examination, screened mug test, CMT (California Mastitis Test) and microbiological examination; verification of installations and hygienic procedures during milking, by a check list, and counts of mesophilic microrganisms on the hands of milkers and utensils, as well as counts of total coliforms, thermotolerant coliforms and E. coli in water used for milking. It was also observed the relationship between the level of adoption of hygienic management against mastitis according of socioeconomic and microbiological aspects evaluated, and between the occurrence of goat mastitis in the properties according socioeconomic, environmental, hygienic and microbiological aspects described. The results showed that most producers, 44,82% e 79,31%, respectively, are inexperienced and have low levels of education, although often participate in training events associated to activity. The properties evaluated are generally small, with rustic installations and small goat herds, which are subject to inadequated sanity and feeding management. Milk yield are low, but present importance as a source of supplementary salary for farmers. The occurrence of mastitis was within the standards expected, and Staphylococcus sp. the main agent isolated. It was observed that the conditions of the installations and hygienic management in the milking are poor, and the bacterial counts of the hands, utensils and water were high in most samples, demonstrating poor sanitary conditions. The level of adoption of hygienic management against mastitis is dependent on characteristics such as training and technical assistance and daily milk production per animal was higher in properties with the best features of this kind of management. While the presence of goat mastitis was not influenced by evaluated variables
Diagnosis of family production of milk goats in Mossoró-RN: social, economic, environmental and sanitary-hygienic aspects
Keywords: Dairy goat; Family farming; semiarid; Caprinocultura leiteira; Agricultura familiar; Semiárido; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE